Calculate Travel Time and Distance with Openstreetmap Data Using the Open Source Routing Machine (OSRM). (June 2016) - Huber, Stephan; Rust, Christoph
In this article, we introduce theosrmtime command, which calculates the distance and travel time between two points using latitude and longitude information. The command uses the Open Source Routing Machine (OSRM) and OpenStreetMap to find the optimal route by car, by bicycle, or on foot. The procedure is specially built for large georeferenced datasets. Because it is fast, the command uses the full computational capacity of a PC, allows the user to make unlimited requests, and is independent of the Internet and commercial online providers. Hence, there is no risk of the command becoming obsolete. Moreover, the results can be replicated at any time.